If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 4)(3x + 5) = 0 Reorder the terms: (4 + 5x)(3x + 5) = 0 Reorder the terms: (4 + 5x)(5 + 3x) = 0 Multiply (4 + 5x) * (5 + 3x) (4(5 + 3x) + 5x * (5 + 3x)) = 0 ((5 * 4 + 3x * 4) + 5x * (5 + 3x)) = 0 ((20 + 12x) + 5x * (5 + 3x)) = 0 (20 + 12x + (5 * 5x + 3x * 5x)) = 0 (20 + 12x + (25x + 15x2)) = 0 Combine like terms: 12x + 25x = 37x (20 + 37x + 15x2) = 0 Solving 20 + 37x + 15x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + 3x)(4 + 5x) = 0Subproblem 1
Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(4 + 5x)' equal to zero and attempt to solve: Simplifying 4 + 5x = 0 Solving 4 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 0 + -4 5x = 0 + -4 Combine like terms: 0 + -4 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8Solution
x = {-1.666666667, -0.8}
| (x+17)(4x+1)= | | 3d+2=-2d-8 | | 6y-18-5y+10=8 | | x-2x=7/1×4/3 | | Y^14/y^6 | | (x^2+x-2)(x^2+x-6)= | | -(0.79l+.227)=-(2.09l+.838) | | 5-2x=34 | | 3x/5=1 | | (c+11)(c-9)= | | 5x/2=1/3 | | 4x^4-20x^3+8x^2= | | (w+4)(w+5)= | | (x^2-2)(x^2-2-3)= | | 5x-2(x-4)=17 | | (c-p)(c-p)= | | 6r+3*4= | | (3b+4f)(3b-4f)= | | 3-2x=37 | | 5/2y-4y/3 | | 5/2x-4x/3 | | x/6=-5/5 | | -2(2l-4)=-4(-l+2) | | 5(2x+6)-47=3(x-15)+16 | | 67/5 | | x^2=2(7x+2) | | 2dc(d+c)= | | 128/120c=15/120 | | 5z(7-x)= | | -8a-(3a+6)=4-a | | 1/4(7x-16) | | 21+3y=o |